HUBUNGAN STATUS GIZI DENGAN PERKEMBANGAN MOTORIK KASAR PADA SISWA TK IT RABBANI BATAM - Sukma Sahreni; Brain Gantoro (Universitas Batam, 2019)
During growth and development, children need good nutrition that can produce energy. Less or more nutrition can interfere with processes in the body, where these processes have an impact on the child's development. One aspect of development that exists in children is the motoric aspect. Motor development in the form of a child's growth and development abilities. Gross motor in the form of body movements that use large muscles or most or all members of the body that are affected by the child's maturity. This study aims to determine the relationship of nutritional status with gross motor development in TK IT Rabbani Batam students in 2019. This research method is observational analytic using a cross-sectional design conducted at TK IT Rabbani Batam. The sampling technique is total sampling with a sample of 54 people. Data collection using measurements of height, weight, and assessment of gross motor development using the DDST II sheet. Data analysis using the Spearman Rank statistical test. There were 2 children with underweight nutritional status consisting of 1 child (50%) with untestable/abnormal gross motor development and 1 child (50%) suspect. There are 38 children with normal nutritional status consisting of 3 children (7.9%) with untestable/abnormal gross motor development, 5 children (13.2%) suspect and 30 children (78.9%) normal. There are 14 children with obesity-obesity nutritional status consisting of 1 child (7.1%) with suspect gross motor development, 13 children (92.9%) normal. Statistical test results of the relationship of Nutrition Status with Gross Motor Development get p-value 0.025. There is a significant relationship between nutritional status and gross motor development in kindergarten IT Rabbani Batam students in 2019.